Developing and Validating a Short-Form Questionnaire for the Assessment of Seven Facets of Conscientiousness in Large-Scale Assessments. Issue 6 (24th October 2022) - Franzen, Patrick; Arens, A. Katrin; Greiff, Samuel; van der Westhuizen, Lindie; Fischbach, Antoine; Wollschläger, Rachel; Niepel, Christoph
Abstract: Conscientiousness is the most important personality predictor of academic achievement. It consists of several lower order facets with differential relations to academic achievement. There is currently no short instrument assessing facets of conscientiousness in the educational context. Therefore, in the present multi-study report, we develop and validate a short-form questionnaire for the assessment of seven Conscientiousness facets, namely Industriousness, Perfectionism, Tidiness, Procrastination Refrainment, Control, Caution, and Task Planning. To this end, we examined multiple representative samples totaling N = 14, 604 Grade 9 and 10 students from Luxembourg. The questionnaire was developed by adapting and shortening an existing scale using an exhaustive search algorithm. The algorithm was specified to select the best item combination based on model fit, reliability, and measurement invariance across the German and French language versions. The resulting instrument showed the expected factorial structure. The relations of the facets with personality constructs and academic achievement were in line with theoretical assumptions. Reliability was acceptable for all facets. Measurement invariance across language versions, gender, immigration status and cohort was established. We conclude that the presented questionnaire provides a short measurement of seven facets of Conscientiousness with valid and reliable scores.